New records of Ulidiidae (Diptera: Tephritoidea) from state of Mato Grosso do Sul, Brazil - Freitas, Devair dos Santos (2025)
This study was conducted in an urban fragment of Cerrado (savannah formation) in the municipality of Campo Grande, Mato Grosso do Sul (MS), Brazil. McPhail traps, with sugarcane extract, were used along one year with the goals to sampling ulidiids flies. As results were presented new occurrences for four genera and seven species of uliidids for MS. Besides sampled four species belongs from three genera previous known from MS. The fauna of uliidids from MS increasing in 140% and 100% the number of the species and genera, respectively. Actually, the fauna of ulidiids from MS is represented by 12 species into eight genera.